Prevalence and its antibacterial susceptibility pattern of asymptomatic bacteriuria in pregnancy of a teaching hospital - Bharat Talukdar; Deepjyoti Kalita; Sangita Deka; Sangita Mahela (Barpeta Obstetrics and Gynaecological Society, 2023)
Objective: The aim of this study was to evaluate the prevalence and risk factors of asymptomatic bacteriuria, to identify commonest microorganisms and their antimicrobial susceptibility in pregnant women. Method: A total of 230 healthy pregnant women who attended antenatal outpatient department for first visit were evaluated for bacteriuria. Results: The prevalence of asymptomatic bacteriuria in pregnant women was 10%. Demographic and obstetric parameters did not significantly influence the prevalence of asymptomatic bacteriuria except in rural dwelling (χ 2 = 4.454, p=0.0348). The dominant bacteria were Escherichia coli (52.17%). Uropathogens were highly sensitive to imipenem and aminoglycosides and less sensitive to nalidixic acid, ampicillin, amoxicillin and cotrimoxazole. Conclusion: There is a high prevalence of asymptomatic bacteriuria among pregnant women in the study. With the exception of rural dwelling, demographic and obstetric parameters did not significantly influence the risk of ASB. Therefore, routine asymptomatic bacteriuria screening among pregnant women is suggested in our environment.